Oxygenation of dog liver transplants as an early indicator of graft failure - Kallinowski, Friedrich; Runkel, Norbert; Senninger, Norbert; Ye, Q. F.; Bleyl, Jörg-Uwe; Otto, Gerd; Herfarth, Christian (European surgical research, 1996)
This study examines the potential value of liver oxygenation as a predictor of early graft function, pO2 measurements were performed on 10 pairs of beagle (donor) and foxhound (recipient) dogs during pentobarbital anesthesis. Two different explantation techniques were used: complete preparation and dissection before perfusion and explantation (group A) or rapid perfusion and explantation with detailed preparation of the liver and dissection of vessels ex situ after explantation (group B). In both groups, the technique of liver perfusion with 1,000 ml arterial and 500 ml portovenous application of ice-cold UW solution was equal. Local oxygen partial pressure values were obtained polarographically with miniaturized needle electrodes. The liver oxygenation directly after laparotomy was comparable in both groups (median values around 54 mm Hg). Prior to the infusion of UW solution, a reduction of the tissue oxygenation values to 24 mm Hg was observed in group A (p < 0.01 compared to postlaparotomy values). In group B, limited preexplantation surgical dissection resulted in a reduced pO2 decline to 42 mm Hg (n.s.). After transplantation, the reduced tissue oxygenation persisted in the livers of the dogs which were completely dissected in situ (group B) as compared to the preexplantation recipient and the donor liver before instrumentation (p < 0.01). In contrast, rapidly perfused livers again exhibited only an insignificant reduction of tissue oxygenation following transplantation. Survival correlated linearly with the liver oxygenation within the observation time after transplantation (p < 0.01). A significant survival advantage was found for the rapid perfusion technique (p < 0.05). We conclude that the tissue oxygenation might provide valuable information on early graft function.
Elektronische Reproduktion der Druck-Ausgabe 24. April 2008
Gesehen am 03.09.2025